Implementation of Online Learning Model at SMA Muhammadiyah 1 Taman - Mutiara Noor Imani; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
This research is motivated by the application of online learning during the Pandemic. The purpose of this study is to describe the implementation of learning during the COVID-19 Pandemic. This research uses descriptive qualitative method. This research was conducted by students majoring in English Education, University of Muhammadiyah Sidoarjo at elementary, junior high, and high school in their respective regions. The COVID-19 pandemic has made changes to various aspects of human life today, especially in the world of education. In the current pandemic era, education in Indonesia is one of the most affected. Online learning has become the most effective solution for learning in the midst of the COVID-19 Pandemic to continue to provide the best service to students. The online education system is not easy. In addition to the personal discipline of self-study, there are facilities and resources that must be provided and paid attention to. In this study, it is hoped that it can be an evaluation for various schools and campuses to further improve the online learning system to be better and more effective.